1988
DOI: 10.1128/aem.54.7.1795-1805.1988
|View full text |Cite
|
Sign up to set email alerts
|

Nonspecific Factors Involved in Attachment of Entomopathogenic Deuteromycetes to Host Insect Cuticle

Abstract: The attachment of the conidia of the insect-pathogenic fungi Nomuraea rileyi, Beauveria bassiana, and Metarrhizium anisopliae to insect cuticle was mediated by strong binding forces. The attachment was passive and nonspecific in that the conidia adhered readily to both host and nonhost cuticle preparations. The hydrophobicity of the conidial wall and the insect epicuticle appeared to mediate the adhesion process. Detergents, solvents, and high-molecular-weight proteins known to neutralize hydrophobicity reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
88
0
10

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(107 citation statements)
references
References 20 publications
3
88
0
10
Order By: Relevance
“…Beauveria bassiana is an insect pathogenic fungus that produces asexually derived hydrophobic conidia (Boucias et al, 1988) that adhere to the insect cuticle, germinate and produce hyphae that penetrate the cuticle via mechanical pressure and cuticle degrading enzymes (St Leger, 1993). Because of its pathogenic properties, B. bassiana is employed as a biological control agent against insect pests.…”
Section: Introductionmentioning
confidence: 99%
“…Beauveria bassiana is an insect pathogenic fungus that produces asexually derived hydrophobic conidia (Boucias et al, 1988) that adhere to the insect cuticle, germinate and produce hyphae that penetrate the cuticle via mechanical pressure and cuticle degrading enzymes (St Leger, 1993). Because of its pathogenic properties, B. bassiana is employed as a biological control agent against insect pests.…”
Section: Introductionmentioning
confidence: 99%
“…The accumulation of electrical charge on the surface of insects has attracted the attention of investigators working on the mechanisms involved in pollinator/pollen interactions,1–5 the attachment of entomopathogens to the host cuticle,6 and the development of novel bioelectrostatic traps 7. An insect may acquire an electrostatic charge in a variety of ways including: (1) frictional charging during flight,4 (2) from a surface by contact and frictional charging (Fig 1),8, 9 (3) induction charging from an electrical field,10 (4) ionic transfer across the cuticle via dermal glands or pore channels11, 12 or (5) attachment of charged particles to the cuticle 10.…”
Section: Introductionmentioning
confidence: 99%
“…5 Pf909 conidial adhesion could be due to hydrophobic interactions, similar to those described for Botrytis cinerea, 32 and fungal entomopathogenic deuteromycetes. 33 The conidial adhesion of Bipolaris sorokiniana, B. cinerea, Colletotrichum graminicola, and Uromyces viciae-fabae appeared to be selective to hydrophobic surfaces as no adhesion was observed to hydrophilic glass surfaces. 30,32,[34][35][36][37] The relationship between spore germination and surface wettability has been investigated in some other studies where it was shown that conidia of C. graminicola 38 or Phyllosticta ampelicida 39 seldom germinate with deficient contact with a hard surface, whereas spores of Colletotrichum lagenarium germinate independently of the contact with surfaces.…”
Section: Discussionmentioning
confidence: 99%